NA 70 JAAR: 'N KORT OORSIG VAN DIE EERSTE WÊRELDOORLOG (1914-1919), MET BESONDERE VERWYSING NA DIE WESTELIKE FRONT EN SUID-AFRIKA SE DEELNAME - Ploeger, Jan (Scientia Militaria - South African Journal of Military Studies, 2012)
In the early part of the 20th century there was a delicate balance of power prevailing among European nations. There were also several treaties between groups of nations whereby an attack on anyone nation would involve several groups. The spark to this powder keg situation occurred when Arch-Duke Ferdinand was assassinated on 28 June 1914. The Austro-Hungarians declared war on Serbia which in turn brought in Russia, Germany, France and Great Britain. Britain's entry brought in the Commonwealth which included South Africa. This condensed history sketches the course of "The Great War" as it became known and highlights the role of the South African Forces.